PENGARUH CORPORATE SOCIAL RESPONSIBILITY, CURRENT RATIO, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Felix, Jonathan Donny; Lusy (Jurnal Akuntansi, 2024)
This study aims to determine and analyse the effect of corporate social responsibility, current ratio, and profitability on the value of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2020. The research method used is quantitative method. Quantitative research methods can be interpreted as methods in the population. This research is usually used to examine certain populations or samples. Data collection using research instruments. The population or subject in this study are companies in the consumer goods industry sector with a total population of 60 companies listed on the Indonesia Stock Exchange. The sampling technique used is saturated sampling. The data was analysed through descriptive statistical analysis, model feasibility test, classical assumption test, multiple linear regression analysis, and coefficient of determination. Hypothesis testing used is the t test statistical method with IBM SPSS 26 software. The results showed that corporate social responsibility, current ratio and profitability affect firm value.